Plug-in constructions as means of expressing ethno-cultural information in artistic texts of a bilingual writer - Tumanova, Ainakul (Przegląd Wschodnioeuropejski, 2018)
The article investigates the means of expression of ethno-cultural information in artistic text, in particular plug-in constructions. It provides a brief overview of scientific sources on this issue. The purpose of the article is to observe how plug-in constructions express additional, explanatory information to the information presented in the artistic text. As a result of analysis of the actual material, the work presents an attempt of generalization and systematization of various types of plug-in constructions and their subspecies. The inserts explain / supplement / specify the contents of a historical event / person; represent important information in the sentence structure/ complex syntactic integer; reflect the inner state of the narrator / character; exhibit the individual-author’s style. To illustrate each type of insertion are given examples from the works of the Russian-speaking writer from Kazakhstan – A. Alimzhanov.